Responding to crisis : a rhetorical approach to crisis communication - Millar, Dan Pyle, 1938-; Heath, Robert L. (Robert Lawrence), 1941- (LEA's communication series., 2004)
Describing a rhetorical approach to crisis communication, this text reviews rhetorical perspective on organizational crisis, raising questions and provoking issues. It aims to add depth and a breadth of understanding to the analysis of the rhetorical implications of a crisis.